PERTUMBUHAN BIBIT KOPI LIBERIKA TUNGKAL KOMPOSIT PADA BERBAGAI MEDIA TANAM - Yulistiati Nengsih; Yuza Defitri (Universitas Batanghari, 2019)
Good planting media is a medium that is able to provider water and nutrients is sufficient quantities for plant growth. This can be found on soils with good air conditioning, has a solid aggregate, good water holding ability and room for sufficient rooting. Proper use of media will provide optimal growth for the plants. This study aims to determine the best planting medium to support the growth of coffe seedling Liberika Tungkal Komposit. The research was conducted in the experimental garden Pijoan, University Batanghari Jambi. From March to May 2017. The research design in this experiment was planting medium with complete randomized environmental design (RAL). The treatment is : M0 = plant medium 100% peat soil, M1 = plant medium 100% ultisol soil, M2 = planting medium 50% untisol soil + 50% rice husk charcoal, M3 = planting medium 50% ultisol soil + 50% cocopeat, M4 = planting medium 50% ultisol soil + 50% river sand, M5 = planting medium 50% peat soil + 50% rice husk charcoal, M6 = planting medium 50% peat soil + 50% cocopeat, M7 = planting medium 50% peat soil + 50% river sand. Parameter observed were plant height, stem diameter, root length, crown dry weight, root dry weight, root canopy ratio, total dry weight, quality index, initial pH media and final pH media. The result showed that the ultisol 100% ultisol garden media gave the heighes seed growth value based on single parameter ie plant height, stem diameter, root lenght, crown dry weight, root dry weight, root canopy ratio, total dry weight, and initial media pH and treatment integrated quality index that indicates that the seed is most ready to be moved to the field.Keywords: nurseries, plantations, coffee AbstrakMedia tanam yang baik adalah media yang mampu menyediakan air dan unsur hara dalam jumlah cukup bagi pertumbuhan tanaman. Hal ini dapat ditemukan pada tanah dengan tata udara yang baik, mempunyai agregat mantap, kemampuan menahan air yang baik dan ruang untuk perakaran yang cukup.Penggunaan media yang tepat akan memberikan pertumbuhan yang optimal bagi tanaman. Percobaan bertujuan untuk mengetahui media tanam yang paling baik untuk menunjang pertumbuhan bibit kopi Liberika Tungkal Komposit. Penelitian dilakukan di Kebun Percobaan Fakultas Pertanian Universitas Batanghari di Pijoan, Muaro Jambi. Percobaan dilaksanakan pada bulan Maret sampai Mei 2017. Percobaan menggunakan rancangan lingkungan acak lengkap dan rancangan perlakuan media tanam (M) sebagai berikut: M0 = 100% gambut, M1= 100% tanah jenis ultisol, M2= 50% tanah jenis ultisol + 50% arang sekam padi, M3= 50% tanah jenis ultisol + 50% cocopeat, M4 = 50% tanah jenis ultisol + 50% pasir sungai, M5= 50% tanah gambut + 50% arang sekam padi, M6= 50% tanah gambut + 50% cocopeat, M7= 50% tanah gambut + 50% pasir sungai. Parameter yang diamati adalah pH awal dan pH akhir media, tinggi tanaman, diameter batang, panjang akar, bobot kering tajuk, bobot kering akar, nisbah tajuk akar, bobot kering total dan indek kualitas. Hasil percobaan menunjukkan media tanam 100% tanah jenis ultisol menghasilkan pertumbuhan bibit tertinggi berdasarkan parameter tunggal yaitu tinggi tanaman, diameter batang, panjang akar, bobot kering tajuk, bobot kering akar, nisbah tajuk akar, bobot kering total dan parameter terintegrasi yaitu indeks kualitas.Kata kunci: pembibitan, perkebunan, kopi